Isomorphic influences and voluntary disclosure: The mediating role of organizational culture - Samson Iliya Nyahas; John C. Munene; Laura Orobia; Twaha Kigongo Kaawaase (Cogent Business & Management, 2017)
Purpose: The purpose of this paper is to test the mediating effect of organizational culture in the relationship between isomorphic influences and voluntary disclosure. Design/methodology/approach: A cross-sectional design was employed. Data were collected using a survey questionnaire for the independent variables of coercive, mimetic normative isomorphism as well as organizational culture (mediating variable). The data for the dependent and control variable were obtained from content analysis of financial reports of 92 companies and was analysed using partial least squares PLSSEM. Findings: The results indicate that coercive and normative isomorphic mechanisms are positively related voluntary disclosure while mimetic mechanism is not. Organizational culture partially mediates the relationship between isomorphic influences and voluntary disclosure practices of listed firms in Nigeria. Research Limitation/implication: The cross-sectional nature of the study means that it does not capture changes in the Nigerian business environment overtime. Future research may consider a longitudinal study. The study is not industry specific as such may capture industry differences. However, the result is still considered valid since industry category was controlled for. Practical implication: the result has implication for a number of interested parties such as regulatory bodies, accounting professional bodies, external auditors academics, and mangers. Originality/value: The study, it has contributed to our understanding of the mediating effect of organizational culture on the relationship between isomorphic mechanisms and voluntary disclosure from the perspective of a developing country like Nigeria.
Keywords: 650